Induction of interleukin 1 secretion by adjuvant-active peptidoglycans. - Vacheron, F (1983)
The ability of differently structured, purified peptidoglycans (PG) to induce interleukin 1 (IL1) secretion was compared. PG from Bacillus megaterium and Staphylococcus aureus stimulated the production of IL1 by mouse peritoneal macrophages and human adherent mononuclear cells, whereas PG from Micrococcus lysodeikticus and Corynebacterium poinsettiae were inactive. There was a correlation between the ability of PG to induce IL1 secretion and previously demonstrated immunoenhancing activities (adjuvant effect, increase of resistance to tumor growth) of PG. PG solubilization by lysozyme decreased but did not abolish the PG effect on IL1 secretion. Active PG induced IL1 production in nude mice and in the C3H/HeJ strain (which is unresponsive to lipopolysaccharides).